2018
DOI: 10.1016/j.sapharm.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Application of process mapping to understand integration of high risk medicine care bundles within community pharmacy practice

Abstract: Understanding CB integration into routine practice has positive implications for successful implementation. The generic process map can be used to develop targeted resources, and/or be disseminated to facilitate CB delivery and foster whole team involvement. Similar methods could be utilised within other settings, to allow those developing novel services to distil the key processes and consider their integration within routine workflows to effect maximal, efficient implementation and benefit to patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, some studies reported how PM helped to promote the integration of health services across different settings by developing clinical evidence-based recommendations agreed among different healthcare professionals [ 74 , 86 , 87 , 89 ]. Finally, studies describe how PM can be a valuable tool for documenting a care process for further dissemination [ 170 ]. This is beneficial, for example, in helping to inform patients and carers about their expected journey [ 75 , 99 , 120 122 ] or to support training and education of healthcare professionals [ 81 , 101 , 152 , 153 , 162 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, some studies reported how PM helped to promote the integration of health services across different settings by developing clinical evidence-based recommendations agreed among different healthcare professionals [ 74 , 86 , 87 , 89 ]. Finally, studies describe how PM can be a valuable tool for documenting a care process for further dissemination [ 170 ]. This is beneficial, for example, in helping to inform patients and carers about their expected journey [ 75 , 99 , 120 122 ] or to support training and education of healthcare professionals [ 81 , 101 , 152 , 153 , 162 ].…”
Section: Resultsmentioning
confidence: 99%
“…The swim lane approach allows for representation of the multiple departments involved in care coordination 22 and is used to identify patient handoffs between departments and to keep track of which personnel are responsible for navigation activities throughout a patient's breast cancer treatment. Although process mapping has proven useful in a variety of single-site and multisite health care delivery contexts, [26][27][28][29][30][31][32][33][34] it has primarily been used in oncology to map processes within a single treatment modality. [35][36][37][38][39] The literature reveals a notable gap in describing the application of process mapping to streamline interdisciplinary processes in cancer care delivery and patient navigation, and there is a dearth of evidence on best practices for collaborative regional process improvement in oncology.…”
Section: Process-improvement Teammentioning
confidence: 99%
“…Two studies explored the implementation of technology or a new service. 66,67 Successful integration of a patient education service within the dispensary workflow using process mapping was reported, 67 and changes in workflow sequences following implementation of robotic dispensing technology increased efficiency and complexity. 66 In relation to the exploration of pre-existing dispensing process, five studies focused on this.…”
Section: Suggestions Posed In Relation To Safety Concernsmentioning
confidence: 99%
“…47,54,57,59,66 Six studies recommended further application of the methods adopted in the study. 40,46,51,56,63,67 Three studies suggested further exploration of models developed within the study. This related to Mandt et al's model of "fast dispensing" and "active dispensing" 55 ; Jahn and Caldwell's CHIPPER framework 45 ; and Harvey et al's sociotechnical model, which stratifies pharmacies into those which are "technically oriented", "socially oriented" or "improvising".…”
Section: Recommendations For Future Research Posed By the Studiesmentioning
confidence: 99%